Agroforestry as Policy Option for Forest-Zone Oil Palm Production in Indonesia - Purwanto, E.; Santoso, H.; Jelsma, I.; Widayati, A.; Nugroho, H.Y.S.H.; Noordwijk, M. van (MDPI, 2020)
With 15–20% of Indonesian oil palms located, without a legal basis and permits, within the forest zone (‘Kawasan hutan’), international concerns regarding deforestation affect the totality of Indonesian palm oil export. ‘Forest zone oil palm’ (FZ-OP) is a substantive issue that requires analysis and policy change. While spatial details of FZ-OP remain contested, we review literature on (1) the legal basis of the forest zone and its conversion, (2) social stratification in oil palm production (large-scale, plasma and independent growers), and (3) environmental consequences of forest conversion to FZ-OP, before discussing policy options in a range of social and ecological contexts. Policy options range from full regularization (as FZ-OP stands could meet international forest definitions), to conditional acceptance of diversified smallholder plantings in ‘agroforestry concessions’, to gradually phasing out FZ-OP and eviction/destruction. A nuanced and differentiated approach to FZ-OP is needed, as certification of legality along supply chains is vulnerable to illegal levies and corruption. Corporate actors trading internationally can avoid use of uncertified raw materials, effectively shifting blame and depressing farmgate prices for domestic-market palm oil, but this will not return forest conditions or stop further forest conversion. We discuss an agenda for follow-up policy research.